Outcome of pneumatic balloon dilatation of lower oesophageal sphincter of oesophagus of patients suffering from achalasia cardia - Islam, ASM Nazmul; Alamgir, Md Razibul; Rahman, Mohammed Atiqur; Kabir, Anwarul; Ahmed, Faruque; Ahmed, Dewan Saifuddin; Masud, Md Hasan; Raihan, ASMA (Bangladesh Medical Journal, 2016)
Achalasia is an oesophageal motility disorder of unknown cause, primarily characterized by absence of peristalsis of the esophageal body and impaired relaxation of lower oesophageal sphincter resulting invariably in dysphagia for solids/liquids or both and regurgitation of undigested foods. The diagnosis is usually made by classical symptoms, barium swallow X-ray of oesophagus or by endoscopy. Goal of treatment is to relieve symptoms, improve esophageal emptying and reduce the risk of associate complications. The two most successful treatment options are pneumatic dilation of lower oesophageal sphincter and surgical myotomy. This quasi-experimental study was carried out from January 2010 to December 2011 involving 31 patients of Achalasia Cardia admitted in the Department of Gastroenterology of BSMMU, Dhaka who underwent pneumatic balloon dilatation. Immediately after pneumatic dilatation all the patients got relief of dysphagia and were discharged from hospital next day. At follow-up 4 weeks after pneumatic dilatation, majority (96.2%) of the patients remained improved symptomatically. Significant weight gain was also found at 4 weeks after pneumatic dilatation. Pneumatic dilatation came out to be a simple, safe and effective method for treating patients with achalasia cardia. Bangladesh Med J. 2015 May; 44 (2): 76-81